2021
DOI: 10.1038/s41467-021-25742-w
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric modulation of LRRC8 channels by targeting their cytoplasmic domains

Abstract: Members of the LRRC8 family form heteromeric assemblies, which function as volume-regulated anion channels. These modular proteins consist of a transmembrane pore and cytoplasmic leucine-rich repeat (LRR) domains. Despite their known molecular architecture, the mechanism of activation and the role of the LRR domains in this process has remained elusive. Here we address this question by generating synthetic nanobodies, termed sybodies, which target the LRR domain of the obligatory subunit LRRC8A. We use these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(61 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…This is thought to occur due to altered electrostatic interactions between subunits via a mechanism, which could also be caused by mechanical stress ( Strange et al, 2019 ). Consistent with this paradigm, a recent study demonstrated that synthetic proteinaceous nanobodies (called sybodies) targeting different LRR epitopes profoundly modulate activation of the native channel by low ionic strength ( Deneka et al, 2021 ).…”
Section: Structural Features Of Volume-sensitive Outwardly Rectifying Anion Channel/volume-regulated Anion Channel Maxi-anion Channel Andmentioning
confidence: 90%
See 1 more Smart Citation
“…This is thought to occur due to altered electrostatic interactions between subunits via a mechanism, which could also be caused by mechanical stress ( Strange et al, 2019 ). Consistent with this paradigm, a recent study demonstrated that synthetic proteinaceous nanobodies (called sybodies) targeting different LRR epitopes profoundly modulate activation of the native channel by low ionic strength ( Deneka et al, 2021 ).…”
Section: Structural Features Of Volume-sensitive Outwardly Rectifying Anion Channel/volume-regulated Anion Channel Maxi-anion Channel Andmentioning
confidence: 90%
“…The uniquely arranged LRR region contains numerous charged amino acids at the contacting surfaces between adjacent subunits ( Deneka et al, 2018 ; Kasuya et al, 2018 ; Kefauver et al, 2018 ; Kern et al, 2019 ; Nakamura et al, 2020 ). Such arrangements may explain the well-known activation by low ionic strength of the native VSOR/VRAC ( Cannon et al, 1998 ; Voets et al, 1999 ; Sabirov et al, 2000 ; Deneka et al, 2021 ) and purified LRRC8 proteins in lipid bilayers ( Syeda et al, 2016 ). This is thought to occur due to altered electrostatic interactions between subunits via a mechanism, which could also be caused by mechanical stress ( Strange et al, 2019 ).…”
Section: Structural Features Of Volume-sensitive Outwardly Rectifying Anion Channel/volume-regulated Anion Channel Maxi-anion Channel Andmentioning
confidence: 97%
“…The overall architecture and subunit folding are the same in all of the LRRC8 structures that have been determined ( Deneka et al, 2021 , 2018 ; Gunasekar et al, 2022 ; Kasuya et al, 2018 ; Kefauver et al, 2018 ; Kern et al, 2019 ; Nakamura et al, 2020 ). The overall architecture of LRRC8 assembles into a hexamer ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 92%
“…Due to recent advances in cryo-EM, the first structure of LRRC8 was reported in 2018, only 4 years after the identification of LRRC8 as the molecular entity of VRAC ( Deneka et al, 2018 ). Since then, six studies reported the LRRC8 structures to date ( Kasuya et al, 2018 ; Kefauver et al, 2018 ; Kern et al, 2019 ; Nakamura et al, 2020 ; Deneka et al, 2021 ; Gunasekar et al, 2022 ). In this review, we describe the structural and functional features of the LRRC8 protein family that were elucidated by those studies and discuss the possible directions of further research in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation